Price Discovery and Captive Supply Implications for Alberta Beef Producers and Feeders - Schroeder, Ted C.; Ward, Clement E. (Kansas State University. North American Institute for Beef Economic Research, 2010)
Concerns about potential impacts of captive supply on fed cattle prices have been present for several years in both Canada and the US. In Canada, the magnitude of concern escalated during closure of the US border to fed cattle trade (May 2003 to July 2005) and has remained at an elevated level. Many producers in both Canada and the US argue that presence of captive supplies results in lower cash fed cattle prices. These concerns have motivated policy proposals targeted toward controlling how fed cattle can be marketed and who can own and feed cattle. However, captive supply arrangements evolved out of economic incentives of cattle producers and beef packers to engage in new business arrangements. Therefore, policies that may curtail such practices are met with considerable opposition by those who enjoy direct benefits from these arrangements. This study was designed to assist Alberta Beef Producers in their assessment of captive supplies and possible action paths. We summarize what we know about the impacts of captive supply on fed cattle markets and identify market information and research needs related to fed cattle markets and captive supply in Canada.
Keywords: Cattle prices; Captive supply; Fed cattle; Canada; United States; Feedlots